Emergent Implications of the ‘Combined School’ Phenomenon: Lessons from the Upgraded Nangula Combined School in Limulunga District, Zambia - Mpofu, Martin; Kakana, Fabian; Mundende, Kasonde; Makondo, Francina; Muleya, Gistered; Simui, Francis (Advances in Social Sciences Research Journal, 2021)
This study was conducted at Nangula Combined school in Limulunga District of Western Province, Zambia. It investigated the emergent implications of the ‘Combined School’ phenomenon through experiences of selected stakeholders of the said school using qualitative methodology and Case Study design. The study sample had 25 participants who were purposively sampled. Key findings of the study revealed that the school had experienced some slight positive changes in infrastructural development. The study also revealed that the introduction of senior secondary classes in the school had been appreciated by all stakeholders as it had reduced some distances that learners cover to access education. On a negative part, the study found that the school had a critical shortage of staff accommodation. The few available houses were in a dilapidated state. Inadequate desks, tables and chairs and weekly boarding facilities also characterized the experiences in this school. Further findings of this study were that the school was understaffed, especially at the primary section, which had three teachers only. Besides, the existence of both primary school trained teachers and secondary school trained teachers in one school enhanced the superiority and inferiority complexes. The school had an inadequate supply of teaching and learning resources coupled with the absence of specialized rooms, technology facilities like mobile network and internet connectivity. Thus, it is recommended that the government should embark on infrastructural development and provide adequately trained teachers. Provision of teaching and learning resources and more desks, chairs and tables should be a priority. It is important also to facilitate the upgrading of teachers who have acquired higher professional qualifications. To curb the inferiority and superiority perceptions that exists between the secondary trained teachers and the primary trained teachers, the study recommends that the two sections be split and work independently.